2000
DOI: 10.4141/s99-091
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into mechanisms leading to the development, spread and persistence of soil water repellency following contamination by crude oil

Abstract: Investigation into mechanisms leading to the development, spread and persistence of soil water repellency following contamination by crude oil. Can. J. Soil Sci. 80: 595-606. We investigated mechanisms by which soil water repellency may develop, spread and persist at old crude oil spill sites. We tested if its development may be due to soil sorption of vapour-phase petroleum compounds, its spread due to mechanical dispersal and mixing, and its persistence due to association of causative agents with humin and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…Whatever breakdown has occurred since has been insufficient to eliminate soil WR. This is in agreement with findings from crude oil-contaminated sites studied in Canada by Roy and McGill (2000), but contrasts the typically shorter-lived increases in soil WR associated with the transformation and condensation of organic compounds in the soil during vegetation fires (Doerr et al, 2000).…”
Section: Soil Water Repellencysupporting
confidence: 87%
“…Whatever breakdown has occurred since has been insufficient to eliminate soil WR. This is in agreement with findings from crude oil-contaminated sites studied in Canada by Roy and McGill (2000), but contrasts the typically shorter-lived increases in soil WR associated with the transformation and condensation of organic compounds in the soil during vegetation fires (Doerr et al, 2000).…”
Section: Soil Water Repellencysupporting
confidence: 87%
“…Examples include waxy substances from leaves [ Passialis and Voulgaridis , 1999], root exudates [ Dekker and Ritsema , 1996a; Doerr , 1998], fungi [ Fidanza et al , 2007], microbes [ Hallett and Young , 1999] and decomposing organic matter [ McGhie and Posner , 1981]. Furthermore soil water repellency might also develop locally because of oil spills [ Roy and McGill , 2000b], extensive oil fires as observed in Kuwait [ Suleiman and Bhat , 2004], or wildfires [ DeBano , 2000]. Recently it has also been shown that regular irrigation applications of treated sewage water can lead to the development of soil water repellency due to dissolved organic substances in the sewage water [ Tarchitzky et al , 2007].…”
Section: Occurrence Origin and Hydrological Effects Of Soil Water Rmentioning
confidence: 99%
“…Although some authors have shown that in naturally occurring water repellent soils, increasing organic matter concentrations are positively correlated with higher water repellency values (Vogelmann et al 2013), researchers investigating soils that have become water repellent due to petroleum contamination have found that water repellency is due more to the kind of SOM rather than the amount (Roy and McGill 2000), and that the addition of organic amendments may reduce water repellency by several orders of magnitude, apparently by increasing the water holding capacity of the soil (Córdova 2010, cited in Adams 2011. This may maintain the in situ water content above the critical threshold at which water repellency becomes manifest.…”
Section: Model For Estimating Wdpt From°api and Oil Concentrationmentioning
confidence: 99%
“…In addition to the type and amount of SOM being correlated with soil hydrophobicity, texture has also been implicated. Generally, soils with higher clay contents are less likely to suffer water repellency in the field, due to the greater surface area available, and greater water holding capacity (Vogelmann et al 2013;Roy and McGill 2000). Thus, it is important to exercise caution when using this particular model-applying only to this soil or other, very similar soils in terms quantity and type of clay and organic matter.…”
Section: Model For Estimating Wdpt From°api and Oil Concentrationmentioning
confidence: 99%